Native Forests Claim for Breeding in Argentina: General Concepts and Their State - Pastorino, Mario Juan (Springer, 2021)
The first genetic studies on forest trees in Argentina were carried out with exotic fast-growing species and in relation to their productive use. These antecedents, conducted mainly by the National Institute of Agricultural Technology (Instituto Nacional de Tecnología Agropecuaria, INTA), date back to the 1950s and were based on field trials of poplars, willows, pines, and eucalypts, which were eventually developed as formal genetic improvement programs (Marcó et al. 2016). It was not until the 1980s that genetic studies of native forest species began. The initial work was carried out at the University of Buenos Aires, where the first doctoral thesis on population genetics of a native forest species (Saidman 1985) was defended. Since the 1990s, new scientific groups commenced to develop with similar lines of research, in several INTA groups and in other national universities such as Comahue, Misiones, and Córdoba, expanding the objects of study to a variety of genera and species.